Longitudinal and Transverse Right Ventricular Function in Pulmonary Hypertension: Cardiovascular Magnetic Resonance Imaging Study from the ASPIRE Registry. (1st September 2015) - Swift, Andrew J.; Rajaram, Smitha; Capener, Dave; Elliot, Charlie; Condliffe, Robin; Wild, Jim M.; Kiely, David G.
Abstract : Right ventricular (RV) function is a strong predictor of outcome in cardiovascular diseases. Two components of RV function, longitudinal and transverse motion, have been investigated in pulmonary hypertension (PH). However, their individual clinical significance remains uncertain. The aim of this study was to determine the factors associated with transverse and longitudinal RV motion in patients with PH. In 149 treatment‐naive patients with PH and 16 patients with suspected PH found to have mean pulmonary arterial pressure of <20 mmHg, cardiovascular magnetic resonance imaging was performed within 24 hours of right heart catheterization. In patients with PH, fractional longitudinal motion (fractional tricuspid annulus to apex distance [f‐TAAD]) was significantly greater than fractional transverse motion (fractional septum to free wall distance [f‐SFD]; P = 0.002). In patients without PH, no significant difference between f‐SFD and f‐TAAD was identified ( P = 0.442). Longitudinal RV motion was singularly associated with RV ejection fraction independent of age, invasive hemodynamics, and cardiac magnetic resonance measurements ( P = 0.024). In contrast, transverse RV motion was independently associated with left ventricular eccentricity ( P = 0.036) in addition to RV ejection fraction ( P = 0.014). In conclusion, RV motion is significantly greater in the longitudinal direction in patients with PH, whereas patients without PH have equal contributions of transverse and longitudinal motion. Longitudinal RV motion is primarily associated with global RV pump function in PH. Transverse RV motion not only reflects global pump function but is independently influenced by ventricular interaction in patients with PH.